(untitled) (Advances in Applied Mathematics and Mechanics, 2018)
This study presents an alternative meshless boundary collocation approach, the singular boundary method (SBM), in conjunction with the image concept for simulating SH wave scattering by the canyon topography. First the image concept is implemented to extend the original semi-infinite domain problems to infinite domain problems. Then the SBM has been used to solve the infinite domain problems. In the SBM it employs the singular fundamental solutions as basis functions and introduces the concept of source intensity factor to regularize the singularities of the related fundamental solutions, which avoids singular numerical integrals in the boundary element method. To demonstrate the effectiveness of the proposed approach for SH wave scattering by the canyon topography, several benchmark examples are considered. The present results are compared with the analytical solutions, the null-field boundary integral equation method.